An unusual variation of a right-sided aortic arch with a common subclavian trunk - Daryn Nguyen; Aditya Srinivasan; Natalia Lowry; Jeffrey Fahl; Michael P. Smith; Amanda S. Khan (Translational Research in Anatomy, 2024)
Introduction: A right-sided aortic arch is a rare congenital cardiovascular anomaly that arises from persistence of the right fourth aortic arch and regression of the left fourth aortic arch. This variation commonly gives rise to an aberrant left subclavian artery (ALSA). In this report, we present an unusual variation of a right-sided aortic arch with an isolated common subclavian trunk (CST). Methods: During a routine dissection of a female cadaver, a right-sided aortic arch variation with an aberrant left subclavian artery was observed. The thorax was further dissected to reveal the right-sided aortic arch and anomalous origin of the ALSA from a CST. Results: The ascending aorta arose from the heart to form a right-sided aortic arch which branched into 1) a CST, 2) a left common carotid artery, and 3) a right common carotid artery. The CST branched into a right subclavian artery and an ALSA which traversed posteriorly to the esophagus to its normal anatomical position. The descending thoracic aorta passed along the right lateral aspect of the vertebral column, traversed posteriorly to the esophagus, and continued descending in its anatomical position through the aortic hiatus. Conclusion: Rare aortic arch congenital anomalies such as a common subclavian trunk predispose the body to numerous clinical complications. A common subclavian trunk can cause cardiovascular complications and gastrointestinal complications due to compression of the esophagus. A deep understanding of the variations in the aortic arch and its branches is necessary for all physicians when managing patients with cardiovascular and upper gastrointestinal symptoms.